Sosialisasi Pentingnya Sertifikasi Halal pada Program Self Declare untuk Berkembangnya Bisnis Bidang Makanan dan Minuman di Kecamatan Jaten Kabupaten Karanganyar - Vivi Sylvia Purborini; Tikka Dessy Harsanty (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Halal products are all goods and/or services related to food, drinks, medicines, cosmetics, chemical products, biological products, genetically engineered products and consumer goods used, used or exploited by the public which have been declared halal in accordance with Islamic law. This activity uses lecture methods, questions and answers, and online registration tutorials. The concept of this service activity is in the form of a workshop or training related to socialization and assistance in registering for the free halal certification program (Sehati) through a self-declaration scheme. The implementation of the self-declaration process in this halal industry covers various aspects, starting from pre-service, ongoing service, to post-service. This process is designed to provide holistic support to MSMEs so that they can understand, fulfill and apply halal standards independently, supporting their business growth in the context of the halal market. From this assistance it is very important to provide education to business actors so that they can guarantee that their products are halal and thayyib. Socialization about the importance of halal products and procedures for halal certification using the self-declaration route must be further improved.